Virtualisation of optical networks utilising squeezing protection: the exact formulation. Issue 20 (1st October 2019) - Assis, K.D.R.; Mesquita, L.A.J.; Almeida, R.C.; Waldman, H.; Hammad, A.; Simeonidou, D.
Abstract : Elastic optical network (EON) is a new technology used for virtualisation of optical networks. In this Letter, a new linear formulation with protection is proposed for the design of EON networks with several virtual optical networks (VONs). The mixed integer linear programming (MILP) formulation integrates the concepts of bandwidth squeezing, grooming and modulation format, and allows different protection capability in each VON. The proposed MILP provides efficient survivability results and resource savings (in terms of the spectrum) for a complete design of EON with virtualisation.